4/3 • 5/3 = 20/9 divided by 2 = 10/9
The opposite of 1/3 = -1/3
the opposite of -7/12 = 7/12
Answer:
A. f(x) = 6x + 9
Step-by-step explanation:
The given equation is:
y - 6x - 9 = 0
We have to write this equation in function notation with x as the independent variable. This means that y will be replaced by f(x) and all other terms will be carried to the other side of the equation to get the desired function notation.
y - 6x - 9 = 0
y = 6x + 9
f(x) = 6x + 9
Therefore, option A gives the correct answer.
<-------------.-------------->
0 1 2 3 4 5 6 7 8 9 10
Answer:
4x / (2x^2+1)
Step-by-step explanation:
g(x)=ln(2x^2+1)
Using u substitution
u= 2x^2 +1
du = 4x dx
g'(x) = d/du ( g(u) du)
We know that the derivative of ln(u) = 1/u since this is always positive
= 1/ u* du
Substituting x back into the equation
g'(x) = 1/(2x^2+1) * 4x
= 4x / (2x^2+1)